The Impact of FOMO on Tiktok Content Marketing Storytelling for One Piece Comic Purchase Decisions - Alberta Adinata; Sudarmiatin Sudarmiatin (International Journal of Economics and Management Sciences, 2025)
Digital transformation has reconstructed the marketing landscape, presenting TikTok as a narrative and affective space in shaping consumption decisions. This study investigates the interaction between Storytelling Marketing (STM), Electronic Word of Mouth (e-WOM), and Fear of Missing Out (FOMO) in mediating One Piece comic purchase intention. With a PLS-SEM approach to 385 respondents, it was found that STM and e-WOM not only have a direct impact on purchasing decisions, but also form a psychological resonance in the form of FOMO which strengthens consumptive urges. TikTok in this case is not just a medium, but an affective field where perceptions, emotions, and social impulses intertwine, blurring the line between narrative and economic decisions. This finding confirms the role of content strategy as a construction of meaning that activates symbolic ownership through collective emotional urgency.